Natural Moralities : a Defense of Pluralistic Relativism. - Wong, David B. (Oxford University Press, USA, 2009)
Introduction. Part One: How Pluralism and Naturalism Make for Natural Moralities. 1. Pluralism and Ambivalence. 2. Pluralistic Relativism. 3. Objections and Replies. Part Two: Constraints on Natural Moralities. 4. Identity, Flourishing, and Relationship. 5. Community and Liberal Theory. 6. Does Psychological Realism Constrain the Content of Moralities?. Part Three: Having Confidence in Our Moral Commitments. 7. Moral Reasons -- Internal and External. 8. Morality and Need. 9. Coping with Moral Difference. Bibliography.